Begonia saxifragoides sp. nov. and two new records of Begonia (Begoniaceae) from northern Vietnam - Bon, Trinh Ngoc; Do, Thi Thanh Ha; Le, Thi Hanh; Lo, Minh Duc; Zimmer, Heidi; Lin, Che-Wei (Phytotaxa, 2023)
Surveys in montane forests in northern Vietnam have revealed one new species and two new records of Begonia. The new species, B. saxifragoides resembles B. minhaniae but is distinguished by the orbicular to reniform (vs. broadly ovate) leaves with rounded (vs. acute to acuminate) apex, the petioles densely covered with pilose or villous (vs. subappressed tomentose), ovary trigonous-globose (vs. trigonous-ellipsoid) and wings pilose or glandular hairs (vs. glabrous or sparsely tomentose). The newly recorded species from Vietnam were B. laotica Y.H.Tan & H.B.Ding previously known from Laos, and B. adscendens C.B.Clarke from India, Myanmar and Laos.